A saúde e segurança dos trabalhadores sob o viés da ciência, tecnologia e sociedade - Tavares, Thiago Daniel Ribeiro (Universidade Federal de São Carlos, 2021)
From an STS perspective, and underpinned by Ulrich Beck and Anthony Giddens´ theory of the Risk Society, this study aims to reflect on their potential to support the implementation of national and international public policies and the creation of norms that seek the health and safety of workers . For this purpose, we bring Brazilian and Portuguese legislation, directives from the European Union (EU) and Conventions of the International Labor Organization (ILO) as evidence of the implementation of this protection. The starting point is that in the corporate environment, managers are increasingly aware of the relevance of quality of life and the need to develop and apply better conditions for the well-being of workers. The issue of safety in the work environment is an important factor, highlighting that by being in a safe and well-kept environment, the risks of accidents and occupational diseases are minimized. The duty of care regarding the physical and mental integrity of employees is the company's obligation, through its managers. It is important to remember that investments in the area of work safety are compensated according to the productivity gains of employees, improving working conditions and realizing the important role of Science and Technology for the implementation and organization of a balanced work environment, development, manufacture and certification of EPI and EPC. Thus, due to the great advances in technology associated with the improvement of education, the requirements regarding working conditions have changed, that is, what was previously tolerated has now become unacceptable, forcing the State to constantly create and update its laws. Proof of this is that with the COVID-19 pandemic, there was a need for reinvention, implementing the need for social and physical distancing and consequent adaptation of the working environment. For that, the Ministerial for Labor, International Labor Organization and Organization Health World Cup had an extremely important role in the risk assessment, creating urgent solutions and guidelines to prevent the spread of the disease and ensuring the safety of workers adopted not only in Brazil but throughout the world.
The health and safety of workers under the bias of science, technology and society
Keywords: Sociedade de risco; CTS; COVID-19; Saúde; Segurança do trabalho; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::DIREITO; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PRIVADO::DIREITO DO TRABALHO